Comparative Analysis of Banking Concentration in Indonesia and Malaysia: Market Structure, Stability, and Policy Implications - Pandu Adi Cakranegara; Purwanto (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Banking industry concentration is a crucial issue because it affects financial system stability, banking risk, and bank performance. Differences in concentration levels between Indonesia and Malaysia reflect distinct market structures, making comparative analysis necessary. This study aims to compare banking concentration in Indonesia and Malaysia and examine its impact on banking risk and performance. A quantitative descriptive method is employed, using concentration indicators such as the concentration ratio and the Herfindahl-Hirschman Index. The results show that banking concentration in both countries contributes to industry stability, but determinants of credit risk differ: in Malaysia, credit risk is mainly driven by economic growth and interest rate changes, while in Indonesia, concentration still significantly affects credit risk. The findings also support the structure-conduct-performance hypothesis, indicating that oligopolistic markets encourage banks to invest in safe assets and adjust lending rates to improve performance. Banking concentration benefits the banking sector and offers policy implications for maintaining financial stability and healthy competition.